The spread of COVID-19 in Germany: An application of the SIRDH model - Lukas Landsgesell; Manfred Stadler (University of Tübingen, Faculty of Economics and Social Sciences, 2020)
The paper studies the current COVID-19 pandemic by applying an adapted epidemiologic model, where each individual is in one of the five states 'susceptible', 'infected', 'removed', 'immune healthy' or 'dead'. We extend the basic model with time-invariant transition rates between these states by allowing for time-dependent infection rates as a consequence of lockdowns and social distancing policies as well as for time-dependent mortality rates as a result of changing infection patterns. Our model proves to be appropriate to calibrate and simulate the dynamics of COVID-19 pandemic in Germany between January and October 2020. We provide deeper insights about some key indicators such as the reproduction number, the effectiveness of non-pharmaceutical interventions, and the development of the infection and mortality rates.
urn:nbn:de:bsz:21-dspace-1096453; hdl:10900/109645
Keywords: I12; I18; 330; COVID-19; SIRDH model; health behavior